(untitled) (Ibrahim Medical College Journal, 2010)
In Bangladesh, limited data are available on paediatric hypertension as well as their normal values. This study was done to assess the level of blood pressure in this population group. A total of 1118 students from class I to X of a selected school were measured twice for systolic and diastolic BP within five minutes interval following a standard protocol. The phase V diastolic blood pressure was recorded. The average of two readings was taken. Age was obtained from the school records. The mean age was 10.53 (± 0.09) years and 46.9% of the recruited students were females. The mean (±SE) and median of systolic and diastolic blood pressure were 97.89 (±0.39) and 97.50 mm Hg and 57.58 (±0.39) and 60.00 mm Hg, respectively. Boys had a significantly higher systolic (99.34 ± 0.56 mm Hg) and diastolic (62.59 ± 0.41 mm Hg) blood pressure than the girls (96.78 ± 0.50 mm Hg systolic BP and 51.54 ± 0.55 mm Hg diastolic BP; P<0.001). Systolic blood pressure was found to be positively correlated with age, height and weight and diastolic blood pressure was correlated with height and weight. Although this study gave us an insight into the paediatric BP situation in a particular school, a community based study with representative sample is recommended to develop a reference data on paediatric blood pressure for our country. Ibrahim Med. Coll. J. 2010; 4(1): 9-12 DOI: 10.3329/imcj.v4i1.5928